2003
DOI: 10.1088/0953-8984/15/29/311
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of hydrogen in Ti–Zr–Ni quasicrystals

Abstract: We report the first straightforward measurements of the diffusion coefficient of hydrogen migrating in icosahedral (i-) quasicrystal ribbons of Ti45Zr38Ni17 and in two-phase bulk samples containing both the i-phase and the Laves phase. It is found that at 273–353 K diffusion obeys Arrhenius’s law with activation energy 0.24 eV and that the ratio of the volumes of the phases changes at hydrogenization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The quasi-lattice constant of a R ¼ 0.522 nm could be derived from the three strongest peaks' position with the following expression [28],…”
Section: Tizrni Quasicrystal Filmmentioning
confidence: 99%
“…The quasi-lattice constant of a R ¼ 0.522 nm could be derived from the three strongest peaks' position with the following expression [28],…”
Section: Tizrni Quasicrystal Filmmentioning
confidence: 99%
“…The coherence length of the quasicrystal-phase grain is calculated by measuring the full width at half maximum (FWHM) value of the (110 000) peak, and was estimated in the range of 140 A $ 200 A, which is shorter than the ones measured by Azhazha et al [22] and Zhang et al [23]. The quasi-lattice constants are decreased (from 5.28 to 5.16 A) as increasing the Ti concentration (from 33 to 55 at%), suggesting that Ti occupies the sites for Zr and reduces the cell sizes due to the smaller atomic size.…”
Section: Resultsmentioning
confidence: 90%
“…Azhazha et al [66] have reported that absorbed hydrogen causes an increase in the electrical resistivity of the amorphous alloy Ti 66 Ni 20 Cu 10 Si 4 . The origin of the excess resistivity may be attributed to electron scattering on the deformed phonon spectrum and the interference of the latter scattering with inelastic scattering of electrons on hydrogen.…”
Section: Introductionmentioning
confidence: 99%